PENGARUH HEDONIC SHOPPING MOTIVATION TERHADAP IMPULSE BUYING PADA TOKO ONLINE: STUDI PADA TOKO ONLINE ZALORA - Lia Octaria Pasaribu; Citra Kusuma Dewi (Center for Economic Studies Universitas Katolik Parahyangan, 2015)
Online shopping, including shopping for fashion goods, has become a trend in Indonesia. One of buyer’s motivations to do online-fashion-shopping is hedonic shopping motivation. This research aims to examine the influence of hedonic shopping motivation on impulse buying process. Using 100 buyers of Zalora (an online shop) as the respondents, this study confirms that hedonic shopping motivation has a significant influence on the impulse buying process. Keywords: Hedonic shopping motivation, impulse buying process, Zalora.